il CNR e i Beni Culturali Intervista a Luigi Nicolais, Presidente del Consiglio Nazionale delle Ricerche CNR - Papi, Luca (Archeomatica, 2014)
The National Research Council (CNR) was founded in 1923 and represents the biggest Italian research entity. The CNR is composed of more than 100 institutes divided into 7 departments with a high degree of interdisciplinary that distinguishes it from all other entities. The mission of the CNR is to "create value through the knowledge generated by research," pursuing through the development of scientific research and the promotion of innovation, the competitiveness of the productive system and the fulfilment of individual and collective needs. In the following interview, we have asked the CNR President, Prof. Luigi Nicolais, to illustrate the skills and strategies of the Entity in the field of conservation, enhancement and enjoyment of cultural heritage.